2011
DOI: 10.1371/journal.pone.0024138
|View full text |Cite|
|
Sign up to set email alerts
|

The Long Life of Birds: The Rat-Pigeon Comparison Revisited

Abstract: The most studied comparison of aging and maximum lifespan potential (MLSP) among endotherms involves the 7-fold longevity difference between rats (MLSP 5y) and pigeons (MLSP 35y). A widely accepted theory explaining MLSP differences between species is the oxidative stress theory, which purports that reactive oxygen species (ROS) produced during mitochondrial respiration damage bio-molecules and eventually lead to the breakdown of regulatory systems and consequent death. Previous rat-pigeon studies compared onl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(40 citation statements)
references
References 76 publications
1
38
0
1
Order By: Relevance
“…5D) ROS production of the zebra finch compared with the mouse might appear contradictory to the initial idea that avian mitochondria produce fewer ROS than mammalian mitochondria. However, this idea has recently been seriously questioned (Montgomery et al, 2011), and our results are in accordance with the results of two recent studies comparing birds and mammals (Montgomery et al, 2011;Kuzmiak et al, 2012).…”
Section: Research Articlesupporting
confidence: 93%
See 1 more Smart Citation
“…5D) ROS production of the zebra finch compared with the mouse might appear contradictory to the initial idea that avian mitochondria produce fewer ROS than mammalian mitochondria. However, this idea has recently been seriously questioned (Montgomery et al, 2011), and our results are in accordance with the results of two recent studies comparing birds and mammals (Montgomery et al, 2011;Kuzmiak et al, 2012).…”
Section: Research Articlesupporting
confidence: 93%
“…Finally, avian mitochondria could be less sensitive than other taxa to mitochondrial uncoupling in terms of ROS production (present study; P.B., unpublished results in Japanese quail). Avian mitochondria are known to differ from mammalian ones in some characteristics, such as ROS production (Ku and Sohal, 1993;Lambert et al, 2010; but see Montgomery et al, 2011) and mitochondrial membrane fatty acid composition (Pamplona et al, 1999;Montgomery et al, 2011). According to this idea, our in vitro results suggest that the ROS production of zebra finch mitochondria is less sensitive to mitochondrial uncoupling than the ROS production of mouse mitochondria, at least when the respiration is fuelled with pyruvate-malate (Fig.…”
Section: Research Articlementioning
confidence: 56%
“…Also, lipid peroxidation products are known to damage nearby macromolecules including proteins, a process that has consequences for aging (Pamplona et al, 1999). These ideas suggest that tropical birds have a low degree of fatty acid unsaturation in their membranes, which might protect them from oxidative damage (Pamplona et al, 1999;Montgomery et al, 2011). In summary, we found that primary cell lines derived from tropical birds are more resistant to some cellular stressors compared with cells from their temperate counterparts.…”
Section: Discussionmentioning
confidence: 70%
“…A previously published method (Levine et al, 1990) (see also Cao and Cutler, 1995;Montgomery et al, 2011) was used to quantify the concentration of protein carbonyls in plasma. Protein carbonyls indicate protein oxidative damage.…”
Section: Evaluation Of Blood Oxidative Statusmentioning
confidence: 99%